FARMAKOLOGIYADA MEDIKAMENTLARGA LINGVISTIK TAVSIF VA ULARNING NOMLANISHI - Achilov Muzaffar Norquliyevich, Hamzayeva Nigorabonu (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, we provide a linguistic description of medicaments in pharmacology and analyze them systematically based on scientific principles. The universal principles of drug nomenclature, specifically the mechanisms of differentiation between international nonproprietary names, chemical nomenclature, and trade names, are discussed in depth. Additionally, the article examines the scientific basis of how naming errors can affect the safety and efficacy of pharmaceutical products. This article holds theoretical and practical significance for pharmacology specialists, pharmaceutical researchers, and students in medical education institutions.